Soluble CD30 Levels in Patients with Rheumatoid Arthritis - Birkan Sonel Tur,; Şebnem Ataman,; Nurben Süldür,; Nurşen Düzgün,; Mesut Birol Atay, (Archives of Rheumatology, 2009)
Objective: We aimed to determine serum soluble CD30 (sCD30) levels in patients with rheumatoid arthritis (RA) and to analyze their clinical significance in these patients. Materials and Methods: The study group consisted of 49 patients who fulfilled the 1987 American College of Rheumatology diagnostic criteria for RA, and 20 age- and gender-matched healthy controls. Morning stiffness (minutes), pain (visual analog scale, 0-100 mm VAS), fatigue (5-point scale), patient's and physician's general health assessment (0-100 mm VAS), number of tender and swollen joints (total 28 joints), disease activity (DAS28 score), and physical function capacity (disability) (Turkish version of the health assessment questionnaire, HAQ) were assessed. Presence of extraarticular manifestations was recorded. Radiographic assessment of hands and feet was evaluated according to the modified Sharp method. Routine laboratory tests, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), rheumatoid factor, immunoglobulins, and complements levels were determined by nephelometry. Serum sCD30 levels of the patients with RA and healthy controls were measured by ELISA. Results: The mean age was 51.1±13.1 years. The mean disease duration was 7.7±5.1 years. The median DAS28 score was 4.3 (2.3-6.8) and the median HAQ score 1.1 (0-3). The serum levels of sCD30 were significantly increased in RA patients (25.1±18.3 IU/ml) compared to healthy controls (17.2±8.1 IU/ml) (p=0.004). The mean serum level of sCD30 was not different between the low active and moderate/high active patient groups. There was a correlation between sCD30 level and extraarticular involvement (p=0.009, r=0.37) and physician's general health assessment (p=0.008, r=0.38). Conclusion: The present data suggest a possible involvement of CD30+ T cells in the immune processes of RA. Serum sCD30 levels might be a helpful tool for the evaluation of Th2 activity in RA. However, the relationship between sCD30 and clinical disease activity remains uncertain. Therefore, we suggest the need for further studies to investigate its clinical importance. (Turk J Rheumatol 2009; 24: 131-5)